Parenting styles and preschool children's development: from network analysis perspective - Han, Jiahao; Yan, Zhixiong (Frontiers in Psychology, 2025)
Preschool children's physical and mental development forms a critical foundation for lifelong growth, with parenting styles playing a pivotal role. Previous research has primarily examined broad associations between parenting styles and general development, leaving gaps in understanding specific subdomain connections. This study investigates the intrinsic relationships and age-related dynamics between six representative parenting styles (Humiliation vs. Respect, Rejection vs. Acceptance, Punishment vs. Motivation, Dictatorship vs. Democracy, Indulgence vs. Control, and Rudeness vs. Protection) and five key developmental domains (Cognition, Emotion, Language, Art, and Body) in a large sample of preschool children. Using network analysis, we evaluated data from 6,394 Chinese parents who completed the Preschool Development Scale (PDS) and Parenting Style Scale (PRSS). Networks were constructed via Extended Bayesian Information Criterion for Graphical Lasso (EBICGLasso), with centrality, bridge analysis, and age-group comparisons (3-, 4-, and 5-year-olds) conducted. Results revealed Motivation (parenting) and Emotion (development) as the strongest Bridge Expected Influence (BEI) nodes. The Motivation-Cognition connection was the most robust across the sample. Age-specific analyses showed distinct bridge patterns: Motivation-Art dominated at age 3, Acceptance-Art at age 4, and Respect-Language at age 5. The strongest cross-cluster link shifted from Motivation-Cognition (ages 3–4) to Respect-Language (age 5). The network invariance test confirmed significant structural differences between all age groups (M > 0.119, p < 0.002). These findings highlight Motivation and Emotion as core bridges between parenting and development, and Motivation–Cognition–Emotion pathway serves as a potential theoretical model that offers explanatory value. Notably, parenting-development connections evolved from direct (Motivation-Art) to indirect (Respect-Language) associations with age. This study advances the traditional focus on global effects by revealing nuanced, age-specific linkages, underscoring the importance of tailored parenting strategies to foster preschool children's development.